Environmental, social, and governance disclosure and firm performance: Evidence from firms listed under the FTSE Bursa Malaysia Top 100 Index - Rosley, Nor Atikah; Muhammad, Kamaruzzaman; Ghani, Erlane K; Sukmadilaga, Citra (Edelweiss Applied Science and Technology, 2023)
This study examines the relationship between ESG and the performance of firms listed in the Financial Times Stock Exchange (FTSE), Bursa Malaysia Top 100 Index in Malaysia. Specifically, this study examines the effect of each of the ESG pillars, namely, environmental, social, and government disclosure, on firm performance. A content analysis was utilised in this study using a fixed effects model over a 6-year period from 2015 to 2020. This study shows that among the three ESG pillars, government disclosure has a significant positive relationship with firm performance as measured by return on assets. On the other hand, environmental and social factors do not significantly influence the performance of the firms listed in the FTSE, Bursa Malaysia Top 100 Index in Malaysia. The findings of this study shed light on the relationship between each ESG pillar and firm performance in the context of Malaysia as an emerging market and from a developing country perspective. Furthermore, this study makes a valuable contribution by presenting empirical data that supports the notion that ESG recommendations facilitate the entry of enterprises into new markets and the expansion of their presence in current markets. Furthermore, it offers valuable insights into the primary determinants that impact the success of an organisation. This helps companies direct more attention towards this particular component and formulate business plans that empower them to optimise the use of ESG data reporting.